Gayo Highland Takengon from 1904 To 1942: A Historical Analysis of Coffee Plantations at the Era of Dutch Colonialism - Sufandi Iswanto; Zulfan Zulfan; Nina Suryana (Paramita: Historical Studies Journal)
This article analyzes the history of Coffee Plantations in Gayo Highland Takengon at the time of the Dutch Colonialism era from 1904 to 1942. This historical research aimed to reveal the social and economic background, history, and the labors' condition of Gayo Highland Takengon Coffee Plantations. The historical method, which consisted of five analytical stages, was used as the method to reconstruct the history of the coffee plantations in Gayo. The findings of the research show that the geographical factors supported Gayo Highland Takengon as the area of the coffee plantation. Coffee was firstly developed at Gayo Highland by Veenhuyzen in 1908. From 1908 to 1918, coffee was a non-commercial commodity and produced on a small scale. In 1918, after the establishment of Wilhelmina Blang Gele Coffee Plantation and other plantations managed by both private and state companies, coffee increasingly became a commercial commodity. Private and state-owned companies started to employ Javanese laborers or popularly known as Jawa Kontrak and Jawa Kolonisasi. The laborers were brought in gradually from Java and bounded by the Labor System based on the Staatsblad 1911 and Staatsblad 1915. Based on these findings, it can be concluded that the geographical factors and the spirit of capitalism had driven the Dutch private and state companies to develop coffee plantations in Gayo Highland by employing the Javanese contract laborers.